2020
DOI: 10.1039/d0dt01620a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Co3−xMnxO4/C nanocages as an efficient sulfur host for lithium–sulfur batteries with enhanced rate performance

Abstract: Capacity reduction mainly caused by the shuttle effect and low conductivity restricts the commercial application of lithium–sulfur batteries (LSBs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Thereby, the strategy of designing polar materials/carbon mediators to a structured high-efficiency sulfur host is becoming an increasingly popular method in the field of LSBs. It is worth noting that MOF-derived composites can be the ideal mediators in the cathodes of LSBs. , For example, the MOF-derived jujube pit-like Fe 3 O 4 /C composite with a conductivity of 0.071 S/m acted as a host of S. The Fe 3 O 4 /C/S cathode delivered 642 mA h g –1 after 300 cycles at 1°C and a low fading rate of 0.072% per cycle . The ZIF-67-derived CoS 2 /C/S electrode with enhanced electrochemical reaction kinetics exhibits a low 0.064% per cycle after 500 cycles at 1°C .…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the strategy of designing polar materials/carbon mediators to a structured high-efficiency sulfur host is becoming an increasingly popular method in the field of LSBs. It is worth noting that MOF-derived composites can be the ideal mediators in the cathodes of LSBs. , For example, the MOF-derived jujube pit-like Fe 3 O 4 /C composite with a conductivity of 0.071 S/m acted as a host of S. The Fe 3 O 4 /C/S cathode delivered 642 mA h g –1 after 300 cycles at 1°C and a low fading rate of 0.072% per cycle . The ZIF-67-derived CoS 2 /C/S electrode with enhanced electrochemical reaction kinetics exhibits a low 0.064% per cycle after 500 cycles at 1°C .…”
Section: Introductionmentioning
confidence: 99%
“…In the high-resolution spectroscopy In 3d spectra of In 2 O 3 @C (Figure d), two dominant peaks at about 445.0 and 452.5 eV correspond to In 3d 5/2 and In 3d 3/2 of In 3+ , respectively, meaning that there is no formation of In metal under the carbonization process. The C 1 s spectra of In 2 O 3 @C (Figure e) are deconvoluted into three bonding energies, associated with C–C (284.8 eV), C–O (286.5 eV), and CC (289.8 eV) . In the overall XPS spectrum (Figure S7a), the peaks of carbon in In 2 O 3 @C are significantly higher than those in In 2 O 3 , indicating the existence of a carbon layer in In 2 O 3 @C. In Figure S7b,c, the spectral comparison of In 3d and 1s between In 2 O 3 and In 2 O 3 @C showed that both peaks of In2O3@C move to a higher binding energy of about 1.1 eV, which may be caused by the carbon layer increasing the oxygen defects in the material.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4a, the characteristic peaks at 284.8, 286.4, and 288.9 eV represent C−C, C−O, and C�C, respectively. 49 The O 1s XPS spectrum in Figure 4b exhibits that the two typical peaks can be split into three different small peaks, the positions are 529.8 (Metal-O), 531.5 (−OH), and 533.5 eV (CO 2 ). 50,51 In Figure 4c, it can be seen from the Co 2p spectrum that the two dominant peaks with satellite peaks refer to Co 2p 3/2 and Co 2p 1/2 , and each main peak can be deconvoluted into two peaks, in which 780.3 and 795.6 eV correspond to Co 3+ , while 781.2 and 797.1 eV correspond to Co 2+ .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%